(untitled) (Physical Education, Health and Social Sciences, 2025)
The most common kind of infection acquired in hospitals is a bacterial urinary tract infection. Additionally, they are to blame for the highest number of patient deaths, hospital stays, and total medical care expenses. Several studies have reported varying degrees of prevalence for Escherichia coli. This study was designed to check the antimicrobial susceptibility pattern of Escherichia coli (E. coli) isolated from urinary tract infected patient. Urine samples were collected and cultured on CLED media to isolate E. coli. Antibiotic susceptibility testing was performed using the Kirby-Bauer disk diffusion method. A total 276 patients were included in this study. E. coli was the most prevalent isolate in both sexes that constitute 116 (42.02%) of total patients. The antimicrobial susceptibility pattern of E. coli against various antibiotics was observed as Fosfomycin showed the highest sensitivity (78.2%), followed by Amikacin (72.6%) and Imipenem (69.1%). In contrast, high resistance was observed with Ampicillin (94.4%), Ceftriaxone (93.5%), and Gentamycin (91.8%). In conclusion, this study offers crucial information about the patterns of antibiotic susceptibility of E. coli isolates from patients with urinary tract infections (UTIs). E. coli strains show resistance to widely used antibiotics, such as beta-lactams, quinolones, cephalosporins and aminoglycosides.